2009
DOI: 10.1007/s00276-009-0600-1
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the median nerve and median artery in the carpal tunnel: prevalence of their anatomical variations and clinical significance

Abstract: There was a high prevalence of bifid median nerve (19%) and PMA (11%) within the tunnel regardless of gender or age. The PMA was more frequent on the left side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 30 publications
4
39
3
2
Order By: Relevance
“…Thus, the early detection of the thrombosed median artery using ultrasonography can result in prompt anticoagulant therapy, thus preventing the need for any surgery or thrombolytic therapy 10. Although Pierre-Jerome, et al observed that the PMA was more frequently observed on the left side 9, no significant differences between the left and right side of the wrists were observed in the present study. We also detected the coexistence of a persistent median artery with a bifid median nerve in the carpal tunnel in most cases.…”
Section: Discussioncontrasting
confidence: 63%
“…Thus, the early detection of the thrombosed median artery using ultrasonography can result in prompt anticoagulant therapy, thus preventing the need for any surgery or thrombolytic therapy 10. Although Pierre-Jerome, et al observed that the PMA was more frequently observed on the left side 9, no significant differences between the left and right side of the wrists were observed in the present study. We also detected the coexistence of a persistent median artery with a bifid median nerve in the carpal tunnel in most cases.…”
Section: Discussioncontrasting
confidence: 63%
“…4,5) The utility of these in surgical decision making process needs further study as endoscopic release might be contraindicated if such abnormalities are identified preoperatively. The superficial location of the median artery and the possibility of separate tunnels for individual divisions precludes endoscopic release in these patients as the chances of iatrogenic injury or incomplete release is high.…”
Section: Discussionmentioning
confidence: 98%
“…One important anatomic variation is a bifid median nerve (Figure 11), which occurs in roughly 20% of individuals and is often associated with a persistent median artery (Figure 12). The median artery arises from the ulnar artery and passes along the ulnar side of the median nerve or, if the median nerve is bifid, generally between the 2 median nerves 28 …”
Section: Nervesmentioning
confidence: 99%